2007
DOI: 10.1303/aez.2007.255
|View full text |Cite
|
Sign up to set email alerts
|

Host plant chemicals serve intraspecific communication in the white-spotted longicorn beetle, Anoplophora malasiaca (Thomson) (Coleoptera: Cerambycidae)

Abstract: Chemical components that attract males in the laboratory were extracted from the female elytra of the white-spotted longicorn beetle, Anoplophora malasiaca (Thomson) (Coleoptera: Cerambycidae), and found to be comprised of several sesquiterpene hydrocarbons. Males located females that had fed on the bark of the host plant Citrus unshiu more frequently than those fed on an artificial diet in the laboratory. Male attraction was also confirmed in the corresponding sesquiterpene fractions of the host plant. The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 38 publications
1
45
0
Order By: Relevance
“…In the white-spotted longicorn beetle, Anoplophora malasiaca (Cerambycidae), Yasui et al 78) demonstrated that host plant sesquiterpenes (e.g. 47 in Citrus leaves) serve as a cue in their intraspecific communication.…”
Section: Plant Signals For Rendezvous Cuesmentioning
confidence: 99%
“…In the white-spotted longicorn beetle, Anoplophora malasiaca (Cerambycidae), Yasui et al 78) demonstrated that host plant sesquiterpenes (e.g. 47 in Citrus leaves) serve as a cue in their intraspecific communication.…”
Section: Plant Signals For Rendezvous Cuesmentioning
confidence: 99%
“…In contrast, there is no behavioral evidence for female-or male-specific sex attractant pheromone of A. malasiaca (Fukaya et al, 1999(Fukaya et al, , 2000(Fukaya et al, , 2004a(Fukaya et al, , b, 2005aAkino et al, 2001;Yasui et al, 2003Yasui et al, , 2007b. Males as well as females attract both sexes.…”
Section: Mate Location In Cerambycidaementioning
confidence: 99%
“…Males as well as females attract both sexes. The attractant is in volatiles derived from host Citrus unshiu (Yasui et al, 2007b(Yasui et al, , 2008. The role of host plant volatiles in A. malasiaca is discussed in detail in the following sections.…”
Section: Mate Location In Cerambycidaementioning
confidence: 99%
See 2 more Smart Citations